Formulating and Characterizing an Exosome-based Dopamine Carrier System - Yavuz, Burcak; Darici, Hakan; Yildiz, Asli Pinar Zorba; Abamor, Emrah Sefik; Topuzogullari, Murat; Bagirova, Melahat; Allahverdiyev, Adil; Karaoz, Erdal (JOURNAL OF VISUALIZED EXPERIMENTS, 2022)
Exosomes between 40 and 200 nm in size constitute the smallest subgroup of extracellular vesicles. These bioactive vesicles secreted by cells play an active role in intercellular cargo and communication. Exosomes are mostly found in body fluids such as plasma, cerebrospinal fluid, urine, saliva, amniotic fluid, colostrum, breast milk, joint fluid, semen, and pleural acid. Considering the size of exosomes, it is thought that they may play an important role in central nervous system diseases because they can pass through the blood-brain barrier (BBB). Hence, this study aimed to develop an exosome-based nanocarrier system by encapsulating dopamine into exosomes isolated from Wharton's jelly mesenchymal stem cells (WJ-MSCs). Exosomes that passed the characterization process were incubated with dopamine. The dopamineloaded exosomes were recharacterized at the end of incubation. Dopamine-loaded exosomes were investigated in drug release and cytotoxicity assays. The results showed that dopamine could be successfully encapsulated within the exosomes and that the dopamine-loaded exosomes did not affect fibroblast viability.
Keywords: DRUG-DELIVERY SYSTEM; BLOOD-BRAIN-BARRIER; PARKINSONS-DISEASE; EXTRACELLULAR VESICLES; MICROVESICLES; DIAGNOSIS; CURCUMIN; THERAPY; Science & Technology - Other Topics